Association of Il-6 With Insulin Resistance in Patients With Type 2 Diabetes Mellitus (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Chronic inflammation has been considered as a culprit for setting pathophysiological changes which result in insulin resistance and type 2 diabetes mellitus. IL-6 is one of the several proinflammatory cytokines proposed to have an association with type 2 diabetes. Very few studies on the role of circulatory IL-6 in diabetes have been published in Bangladesh. To see the association of IL-6 with insulin resistance in type 2 diabetes mellitus.Materials and methods: A hospital-based cross-sectional observational study was carried out in the Department of Biochemistry, Chittagong Medical College, Department of Endocrinology of Chittagong Medical College Hospital and Chattogram Diabetic Hospital. One hundred (100) type 2 diabetes mellitus patients were included in the study by non-probability consecutive sampling.  Important variables in this study were serum IL-6, BMI, waist circumference and duration of Diabetes Mellitus.   Results: The mean serum IL-6 level > 5 pg/ml and total IL-6 was 10.90±0.37 pg/ml and 10.08±0.39 respectively in patients with type 2 Diabetes Mellitus. The mean HOMAIR was 5.56±0.29 in patients with type 2 diabetes mellitus.   IL6 more than 5 pg/ml was more likely to have increased waist circumference than IL6 £5 pg/ml group. Increased IL6 was more likely to have severe insulin resistance in patients with type 2 diabetes. 74% of the positive outcome would be correctly predicted by the IL-6 value if the value was above or equal to 7.51.Conclusion: The study results showed higher concentrations of serum IL-6 in the diabetic group when compared with a previous reference value. It suggests that IL-6 being an inflammatory mediator might be responsible for some underlying changes which may contribute to the development of insulin resistance in type 2 diabetes.JCMCTA 2024 ; 35 (2) : 135-140